The Use of Hadith in Islamic Boarding School Education - Ahmad Mahfudh; Ahmad Mohammad Tidjani; Fitriyah (GURUPEDIA: Journal of Teacher and Education, 2026)
This research examines the utilization of Hadits in pembelajaran pesantren as the foundation for forming the Islamic character of students. Hadits serves as the main basis for kitab kuning such as Riyadhus Shalihin and Bulughul Maram, taught through memorization, talaqqi, and musyafahah methods that maintain the authenticity of scholarly chains, with the central role of the kiai as both a model and authority in transmission. The values of Hadits like humility (tawadhu), discipline, and brotherhood (ukhuwah) are internalized in worship ethics, education, social interactions, and the students' environment through the living practice of Hadits. Amid modernization, pesantren integrate Hadits studies with formal curricula, digital technology, and contemporary approaches to ensure relevance in the global era. This qualitative library-based approach affirms that pesantren are adaptive in preserving tradition while facing contemporary challenges.